The Effects of Cash and In-Kind Transfer by Religious Organizations on Muslim Households’ Expenditure: Indonesian Family Life Survey 2014 - Hasanah, Alfiah; Apriliano, Muhammad Hilmy; Adam, Asep Muhammad (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
Cash and in-kind transfers are two of the instruments utilized in an endeavor to further expand the economy and solve household welfare concerns. Aside from the government social security program, religious organizations provide a few informal cash and in-kind transfers to largely disadvantaged households. The primary goal of this research is to investigate the effect of cash and in-kind transfers from religious organizations on the consumption expenditures of Muslim households. The Indonesian Family Life Survey (IFLS) 2014 data is used. Using the Ordinary Least Squares method, this study discovers that Muslim households spend the cash and in-kind transfers from religious organizations on two types of household expenditure, namely personal expenditure and utility expenditure, due to the minimal disbursement. The subsidies distributed by the religious organization had a favorable impact on the consumption of Muslim households. An implication of the results is that Muslim households receiving cash and in-kind transfers from religious organizations became opportunities to smooth consumption expenditure. However, these two expenses made just a minor contribution to the overall household cost, so it is necessary to consider other potential impacts, such as savings, investment, or overall household welfare, on the fulfillment of needs that affect expenditure in Muslim households.